L-carnitine: a partner between immune response and lipid metabolism ? - Giuseppe Famularo; Sonia Tzantzoglou; Gino Santini; Vito Trinchieri; Sonia Moretti; Aleardo Koverech; Claudio De Simone (Mediators of Inflammation)
The authors demonstrated that in vivo administered L-carnitine strongly ameliorated the immune response in both healthy individuals receiving Intralipid and ageing subjects with cardiovascular diseases, as shown by the enhancement of mixed lymphocyte reaction. Notably, in the latter group L-carnitine treatment also resulted in a significant reduction of serum levels of both cholesterol and triglycerides. Therefore, the hypothesis is that L-carnitine supplementation could ameliorate both the dysregulated immune response and the abnormal lipid metabolism in several conditions.